Struktur Komunitas Ekosistem Mangrove di Desa Daruba Pantai Kabupaten Pulau Morotai - Djainudin Alwi; Kismanto Koroy; Erik Laba (Peneliti.net, 2019)
The condition of mangrove ecosystems in the coastal areas of Daruba Pantai Village is increasing under pressure both physically and ecologically. The still low awareness of the community to maintain the preservation of mangrove ecosystems well as increasing economic needs, triggers a decline in the extent and quality the environment of mangrove forests. The aim to determine the composition of species and structure of mangrove ecosystem communities. This research was conducted in the mangrove ecosystem area of ​​Daruba Pantai Village, Morotai Island Regency in September - October 2019. The data collection technique used was the observation method and field sampling using the transect plot method. Date were analyzed using quantitative descriptive methods for the composition of mangrove species and mangrove community structure analysis using formula according to (Bengen, 2001) including; type density, relative density, frequency, relative frequency, closure, relative closure, and important values. The results showed that the composition of Mangrove species were found many as 9 species consisting of 5 families Rhizohoraceae as many as 5 species, while the family Rubiacea, Sonneratiaceae, Myrsinaceae, Combertaceae each type 1 type. While the results of community structure analysis of the importance and individual densities of the mangrove species found in the research location at all growth rates are still dominated by Rhizophora stylosa species, indicating that this species is able to adaptation to environmental changes and habitat suitability.